METHODS OF CLASSIFICATION OF ELECTROENCEPHALOGRAM DATA FOR IDENTIFICATION OF HUMAN EMOTIONAL STATE - Holoborodko, V.S.; Lyfar, V.O. (Sworld-Us Conference proceedings, 2025)
The developed methods for classifying electroencephalogram (EEG) signals enable the identification of brain responses to emotional stimuli, which serves as the foundation for constructing neurointerface systems. The result of the classification process is